2010
DOI: 10.1161/circulationaha.110.973784
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of 1 Year of Progressive and Vigorous Exercise Training in Previously Sedentary Individuals Older Than 65 Years of Age

Abstract: Background Healthy but sedentary aging leads to cardiovascular stiffening, whereas life-long endurance training preserves left ventricular (LV) compliance. However, it is unknown whether exercise training started later in life can reverse the effects of sedentary behavior on the heart. Methods and Results Twelve sedentary seniors and 12 Masters athletes were thoroughly screened for comorbidities. Subjects underwent invasive hemodynamic measurements with pulmonary artery catheterization to define Starling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
211
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(224 citation statements)
references
References 59 publications
10
211
2
1
Order By: Relevance
“…Specifically, the typically lower initial baseline VO 2max in the old subjects mathematically biases this assessment of improvement in favor of the older subjects. Therefore, previous studies have indeed revealed robust improvements in VO 2max , presented as a percentage change, of 10-30 % in older subjects after training interventions lasting between 8 weeks and 1 year (Coggan et al 1992;Fujimoto et al 2010;Kohrt et al 1991;Makrides et al 1990;McGuire et al 2001b;Murias et al 2010;Osteras et al 2005). These percentage improvements in VO 2max are comparable, if not even higher than the improvements sometimes documented in young subjects Makrides et al 1990;Murias et al 2010).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Specifically, the typically lower initial baseline VO 2max in the old subjects mathematically biases this assessment of improvement in favor of the older subjects. Therefore, previous studies have indeed revealed robust improvements in VO 2max , presented as a percentage change, of 10-30 % in older subjects after training interventions lasting between 8 weeks and 1 year (Coggan et al 1992;Fujimoto et al 2010;Kohrt et al 1991;Makrides et al 1990;McGuire et al 2001b;Murias et al 2010;Osteras et al 2005). These percentage improvements in VO 2max are comparable, if not even higher than the improvements sometimes documented in young subjects Makrides et al 1990;Murias et al 2010).…”
Section: Discussionmentioning
confidence: 78%
“…Although this decline in aerobic capacity with increasing age is often considered to be inevitable, it seems that this fall can be decelerated, maintained, or even reversed in the elderly by maintaining a high level of physical activity (Faulkner et al 2008;Fujimoto et al 2010;Grimsmo et al 2010;Heath et al 1981;McGuire et al 2001b;Murias et al 2010;Osteras et al 2005;Posner et al 1986;Rogers et al 1990;Trappe et al 2013;Trappe et al 1996). Indeed, marathon running times of approximately 2.5 h or less, documented in males older than 60 years of age, reveal that a VO 2max of ∼70 mL min kg −1 (Helgerud 1994;Tokmakidis et al 1987), a high value exhibited by young endurance athletes at the peak of their careers, is still feasible with increasing age.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest a lack of exercise stimulation, most likely due to a lack of exercise volume and intensity, resulting in an attenuation of alterations commonly expected in regularly exercising subjects. Others have previously noted a lack of LV alterations with regularly exercising subjects (Fujimoto et al 2010;Gates et al 2003). Of note, fractional shortening was different between groups throughout the lifespan (ATFL/CFL and SHAMSED vs. CFL and SHAM) primarily due to alterations to LV EDD.…”
Section: Discussionmentioning
confidence: 87%
“…In older healthy subjects, it has been demonstrated that physical training ameliorates age-related deterioration of cardiac function in terms of enhanced left ventricular systolic function and increased diastolic filling (Spina et al 1998). One year of endurance exercise training led to an increase in exercise cardiac output due mainly to increase in stroke volume (Fujimoto et al 2010). However, it is still uncertain whether the age- Sleep bout number at e nighttime and f daytime.…”
Section: Discussionmentioning
confidence: 99%